Impactos do isolamento social na vida de pessoas idosas: uma análise das condições cognitivas e psicossociais após um ano e meio de pandemia da COVID-19 - Vicentini, Mariana Santucci (Universidade Federal de São Carlos, 2022)
Social isolation was an important preventive measure of the COVID-19 pandemic, especially for risk groups, such as the elderly. However, despite having an epidemiological advantage, social isolation can cause anxiety, depression, fear, insecurity, insomnia, lack of appetite and fatigue, among others.The present study aimed to evaluate the psychosocial impacts of social isolation in the elderly, as well as the use of technology and social connections during the COVID-19 pandemic. This is a retrospective, cross-sectional, observational, comparative and longitudinal study with a quantitative data approach. Nineteen elderly people, who have been attending a Community Center were evaluated, they participated in a gerontology workshop and had a multidimensional evaluation carried out in 2019. After 1 and a half year of pandemic, in 2021, these were re-evaluated in a remote format, during activities suspension of the Community Center. Data from assessments of the presence of depressive symptoms, cognition, social support and family functionality were compared before and after the pandemic. The variables: pandemic impacts, use of technology and social connections were correlated with sociodemographic and psychosocial aspects. As a result, it was possible to identify that, in general, the elderly presented high levels of family functionality and social support during the pandemic period. No increase in depressive symptoms and worsening of cognition were identified in comparisons before and after the pandemic. The use of technology during this period was correlated with age, education and cognition. Furthermore, the use of technology by this group during the COVID-19 pandemic was shown to be correlated with younger age and better cognition. Based on the study results, it is concluded that the social isolation imposed by the COVID-19 pandemic did not compromise the psychosocial and cognitive aspects of those attending the Community Center.
Social isolation impacts on the lives of elderly people: a cognitive and psychosocial analysis after one and a half year of covid-19 pandemic
Keywords: Isolamento social; Vírus da SARS; SARS virus; idoso; Aged; Social isolation; CIENCIAS DA SAUDE